2022
DOI: 10.29333/iji.2022.15339a
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Entrepreneurship Education and the Fear of Failure

Abstract: Studies on the impact of innovation for entrepreneurship indicate that innovation is important to foster businesses through new or improved services, products or processes. However, from a gender perspective, lack of competitiveness and innovativeness has proven to destructively affect entrepreneurs, which in many cases led to failure. There is a gap in literature on the necessity for entrepreneurship educators for a gendered educational approach, targeting the perceived fear of failure and its impact on entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Next, role models have been a common variable in research on entrepreneurship. Extensive empirical studies have shown that entrepreneurial role model is positively related to entrepreneurial intention (Abbasianchavari & Moritz, 2021;Ferreto et al, 2018;Guelich, 2022;Nowiński & Haddoud, 2019;Van Trang et al, 2019;Vodă, Haller, Anichiti, & Butnaru, 2020). Whether it is the entrepreneurs themselves or a startup company, the presence of entrepreneurial role models positively influences the decision to become entrepreneurs (Boldureanu, Ionescu, Bercu, Bedrule-Grigoruţă, & Boldureanu, 2020;Kong et al, 2020;Li & Wu, 2019;Wyrwich et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Next, role models have been a common variable in research on entrepreneurship. Extensive empirical studies have shown that entrepreneurial role model is positively related to entrepreneurial intention (Abbasianchavari & Moritz, 2021;Ferreto et al, 2018;Guelich, 2022;Nowiński & Haddoud, 2019;Van Trang et al, 2019;Vodă, Haller, Anichiti, & Butnaru, 2020). Whether it is the entrepreneurs themselves or a startup company, the presence of entrepreneurial role models positively influences the decision to become entrepreneurs (Boldureanu, Ionescu, Bercu, Bedrule-Grigoruţă, & Boldureanu, 2020;Kong et al, 2020;Li & Wu, 2019;Wyrwich et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Gender. Gender has been the focus of many studies on EFoF, revealing notable variations across contexts and populations, including college students [ 41 , [93] , [94] , [95] , [96] ]. The prevailing view suggests that women tend to perceive higher EFoF levels than males.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fear of failure has been identified as a significant deterrent for women initiating entrepreneurial activities (Cañizares and García, 2010). Entrepreneurship education can mitigate this fear, fostering more innovative entrepreneurial activities, positively influencing entrepreneurial intent, and helping bridge the gender gap in entrepreneurial identity (Elliott et al, 2021;Guelich, 2022). Studies also suggest that implementing regulations against gender discrimination in both public and private sectors could foster an environment conducive to entrepreneurial culture among women (Ge et al, 2022).…”
Section: The Relationship Between Education and Female Entrepreneursh...mentioning
confidence: 99%
“…On the other hand, depending on the context in which it is generated, education may involve high levels of education, specific training courses, or general cultural education. As for the relationship between these two variables (RQ2), what emerges is that education plays a pivotal role in female entrepreneurship and innovation (Elliott et al, 2021;Guelich, 2022). Educational strategies focusing on entrepreneurial skills can help mitigate female entrepreneurs' barriers, fostering innovation and bridging the gender gap in entrepreneurial identity.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%